Congenital diaphragmatic hernia. - José Muñiz Escarpanter; Liván Veitía Collazo (Medisur)
The congenital diaphragmatic hernia is one of the main causes of respiratory distress tributaries of surgical treatment in newborns. Its rate is estimated among 1 x 2000 to 1 x 5000 born alive. At the University Pediatric Hospital ";José Luis Miranda";, Santa Clara, Villa Clara, has been calculated in the period of 1993 to 2001 in 1 x 3571 births. The mortality is high, around the 50%. In US the rank of survival varies from 39 to 95%, with an average of 69%. Those that debut after 24 hours is less than 10%. In those initiated with severe neonatal respiratory distress is greater than 80%, being to this group exactly where the majority of patients are included. We presented the Good Clinical Practices Guideline for Congenital diaphragmatic hernia, approved by consensus in the 1st National Good Clinical Practices Workshop in Pediatric Surgery (Cienfuegos, Cuba, March 7 – 9, 2002).